In vitro shoot regeneration from leaf explants of kenaf (Hibiscus cannabinus L.) - Samanthi, P.W.; Mohd Puad, A.; Suhaimi, N.; Kumar, S.M.; Nor Aini, A.S. (Universiti Kebangsaan Malaysia, 2013)
Kenaf (Hibiscus cannabinus L.) is a versatile plant with multiuse ranging from animal feed to a wide variety of biocomposite products such as pulp and paper and fibre reinforce plastic. Therefore genetically improved planting materials are needed to tailor made requirement of the industry. Thus, development of plant regeneration through callus is important for in vitro genetic manipulation of kenaf. Currently development of successful genetic transformation of kenaf is through in planta transformation means. In vitro shoot regeneration was conducted using leaf explants from varieties V36 and G4 treated to three different combinations of N6 Benzyl adenine (BA) and Indole-3-butyric acid (IBA). High percentage of healthy callus induction was produced in MS medium supplemented with combination of 1.5 mgL-1 BA and 0.5 mgL-1 IBA. In addition 68.7% plant regeneration was obtained in MS medium supplemented with 0.3 mgL-1 GA3. All plantlets produced roots in hormone free medium. There was no significant difference among varieties in terms of callus induction (number of callus) and plant regeneration (number of plantlets). This protocol is useful to be used for the development of gene transformation protocol of kenaf through callus.